2018
DOI: 10.1126/science.aar7389
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of human P-glycoprotein in the ATP-bound, outward-facing conformation

Abstract: The multidrug transporter permeability (P)-glycoprotein is an adenosine triphosphate (ATP)-binding cassette exporter responsible for clinical resistance to chemotherapy. P-glycoprotein extrudes toxic molecules and drugs from cells through ATP-powered conformational changes. Despite decades of effort, only the structures of the inward-facing conformation of P-glycoprotein are available. Here we present the structure of human P-glycoprotein in the outward-facing conformation, determined by cryo-electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
430
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(462 citation statements)
references
References 67 publications
30
430
2
Order By: Relevance
“…Therefore, the substrate-induced conformational changes are transmitted from the TMD to the NBD, and vice versa, which finally result in switching of the TMDs between two alternating conformations, as described by the generally accepted ‘alternating access model’. Available crystal structures of several ABC proteins provide support for this model [6, 14, 15], however the molecular mechanisms by which conformational changes are transduced between the NBD and the TMD are difficult to understand, especially in proteins like Pgp where all four domains are present in the same polypeptide [3]. The architecture of the DrrAB transporter is, however, different in that the NBD and the TMD are present on separate subunits.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the substrate-induced conformational changes are transmitted from the TMD to the NBD, and vice versa, which finally result in switching of the TMDs between two alternating conformations, as described by the generally accepted ‘alternating access model’. Available crystal structures of several ABC proteins provide support for this model [6, 14, 15], however the molecular mechanisms by which conformational changes are transduced between the NBD and the TMD are difficult to understand, especially in proteins like Pgp where all four domains are present in the same polypeptide [3]. The architecture of the DrrAB transporter is, however, different in that the NBD and the TMD are present on separate subunits.…”
Section: Introductionmentioning
confidence: 99%
“…For 6C0V, a new molecular structure of human P-gp was inferred to have an ATP-bound, outward-facing conformation. The researchers further found that the binding of ATP and NBD sites promoted drug release rather than hydrolysis [43]. Therefore, we chose 6C0V as a protein stereo structure model for binding drugs to NBD.…”
Section: Discussionmentioning
confidence: 99%
“…This cavity then rearranges to extrude the substrates from am uch more constrained cavity towards the cell exterior. [20] On the other hand, metabolism and in vivo pharmacokinetics are influenced by chirality.I nhibition of most of the cyto-chromeP 450 isoformsi sa lso strongly influencedb yt he stereochemistry with the exception of isoform3 A4. Isoform 3A4 has am arkedly weaker dependence and this likely reflectst he fact that 3A4 is another system that employs al arge, open and flexible cavity.…”
Section: Why Is Racemisation Important For Drug Discovery?mentioning
confidence: 99%
“…The lack of discrimination between enantiomers for the active processes is in line with recent structural findings suggesting that P‐glycoprotein efflux transporter PGp presents a large open (undiscriminating) cavity to the cell interior into which substrates can move. This cavity then rearranges to extrude the substrates from a much more constrained cavity towards the cell exterior …”
Section: Introductionmentioning
confidence: 98%